Human Factors and Ergonomics in Consumer Product Design : Methods and Techniques. - Karwowski, Waldemar (Handbook of Human Factors in Consumer Product Design., 2011)
The second volume in this set, this book presents case studies of human factors applied to the design of a range of consumer products including white goods, entertainment systems, personal audio devices, mobile phones, gardening products, and computer systems used for leisure. The book focuses on the important perspective human factors brings to consumer product design as well as the different approaches to the design process. It enables readers to follow the design processes and use them for their own work, making the book informative and practical.